The impact of intermittent and continuous training on the levels of CIDE and Perilipin-1 proteins and their effect on the size of lipid droplets in the visceral adipose tissue of obese male rats - Yan Bai; Xiao Yang; Jian Li (Asociación Española de Ciencias del Deporte, 2024)
Intense interval training and moderate-intensity continuous exercise produce lipid droplets that change size and impact visceral adipose tissue. 50 male Wistar rats were divided into 5 groups, each consisting of 8 rats, in order to accomplish this objective. Regarding dietary intake, 2 clusters of 32 rats were subjected to a normal or elevated fat diet over 10 weeks. Post the induction of obesity, 16 animals were euthanized, with an equal number originating from both the high-fat and normal diet cohorts. The ramifications of a high-fat diet were examined through the utilization of samples. The remaining 24 rats were randomly allocated to 3 groups: a sedentary high-fat diet control group, a high-intensity interval training (HIIT) protocol group, and a moderate-intensity continuous training (MICT) protocol group. The 12-week training program had 5 sessions per week. Western blot measurement of perilipin-1, CIDE, and Oil-Red proteins assessed lipid droplet size. Research indicates that HIIT and MICT training significantly decreased CIDEc protein levels (p<0.05) but not CIDEa. CIDEc protein upregulation and perilipin-1 downregulation cause obesity in high-fat diets. HIIT and MICT training reduce fat droplet size and CIDEc protein production. Enhancing perilipin-1, which breaks down fats, may reduce obesity by lowering lipid droplets and weight.